DcABF3, an ABF transcription factor from carrot, alters stomatal density and reduces ABA sensitivity in transgenic Arabidopsis. (January 2021) - Wang, Ya-Hui; Que, Feng; Li, Tong; Zhang, Rong-Rong; Khadr, Ahmed; Xu, Zhi-Sheng; Tian, Yong-Sheng; Xiong, Ai-Sheng
Highlights: DcABF3, an ABA-responsive element-binding transcription factor, was cloned and functionally characterized. DcABF3 alters drought tolerance by increasing stomatal density in Arabidopsis . DcABF3 reduces ABA sensitivity in transgenic Arabidopsis . Abstract: Abscisic acid-responsive element (ABRE)-binding factors (ABFs) are important transcription factors involved in various physiological processes in plants. Stomata are micro channels for water and gas exchange of plants. Previous researches have demonstrated that ABFs can modulate the stomatal development in some plants. However, little is known about stomata-related functions of ABFs in carrots. In our study, DcABF3, a gene encoding for ABF transcription factor, was isolated from carrot. The open reading frame of DcABF3 was 1329 bp, encoding 442 amino acids. Expression profiles of DcABF3 indicated that DcABF3 can respond to drought, salt or ABA treatment in carrots. Overexpressing DcABF3 in Arabidopsis led to the increase of stomatal density which caused severe water loss. Expression assay indicated that overexpression of DcABF3 caused high expression of stomatal development-related transcription factor genes, SPCH, FAMA, MUTE and SCRM s. Increased antioxidant enzyme activities and higher expression levels of stress-related genes were also found in transgenic lines after water deficit treatment. Changes in expression of ABA synthesis-related genes and AtABI s indicated the potential role of DcABF3 in ABA signaling pathway. Under the treatment of exogenous ABA, DcABF3 -overexpression Arabidopsis seedlings exhibited increased root length and germination rate. Our findings demonstrated that heterologous overexpression of DcABF3 positively affected stomatal development and also reduced ABA sensitivity in transgenic Arabidopsis .